Programmable Building of Radially Gradient Nanofibrous Patches Enables Deployment, Bursting Bearing Capability, and Stem Cell Recruitment. (12th November 2021) - Du, Jingtao; Yao, Yueming; Wang, Maidi; Su, Ruigong; Li, Xiaoran; Yu, Jianyong; Ding, Bin
Abstract: Fibrous patches capable of withstanding bursting force and recruiting endogenous stem cells are of great demand for wound treatment. A programmable strategy for development of radially gradient nanofibrous patches with rapid deployment property, robust bursting bearing capability, and excellent mesenchymal stem cell (MSC) recruitment capability, is demonstrated. Benefiting from the royal water lily‐like radially branched architecture, the gradient fibrous (GF) patches exhibit fast deployment in aqueous solution (2 s), high bursting strength of 4.6 N, as well as "center‐to‐periphery" gradient immobilization of stromal‐cell‐derived factor 1α (SDF1α). The SDF1α gradient patches direct MSC migration from the periphery to the center along the aligned nanofibers, resulting in a 4.2 times higher migrated cell number and 2.6 times greater maximum migration distance than random fibrous patches with homogenous SDF1α. The gelatin methacryloyl coated GF patches respond to matrix metalloproteinase‐9 for "on‐demand" release of anti‐inflammatory drug diclofenac sodium (DS). Furthermore, repair of the mouse full‐thickness skin incision validates that SDF1α/DS/GF patches are able to provide feasible microenvironment to attenuate inflammation and improve endogenous MSC recruitment, leading to accelerated wound healing. This work may open a new pathway for development of smart tough fibrous patches for stimulating endogenous repair mechanisms during tissue regeneration. Abstract : A type of bioinspired radially branched nanofibrous patch with "center‐to‐periphery" gradient release and on‐demand release is developed using a straightforward and programmable strategy. The patches exhibit rapid deployment, high bursting strength, enhanced mesenchymal stem cell migration from the periphery to the center, and promote mouse wound healing eventually, indicating great promise as wound care dressings and tissue repair patches.